Aneurysmal Bone Cyst of the Temporal Bone: A Case Report with Review of Literature - Gani, Md Osman; R., Shridhar K.; Chakraborty, Addway; Basu, Abhishek; Mondal, Janmenjoy (Indian Journal of Medical and Paediatric Oncology, 2025)
Aneurysmal bone cysts (ABCs) are noncancerous growths that often develop in the metaphyseal region of long tubular bones. As a whole, ABCs consist of cystic cavities containing blood and hemosiderin enclosed in a subperiosteal shell of reactive bone with septae but not endothelium. Though nonmalignant, ABCs can grow aggressively and be locally destructive, leading to pathologic fractures. Early intervention with surgery is preferred to avoid pathological fractures. Radiotherapy must be considered in inoperable and recurrent cases. ABCs are more common in pediatric patients and cause more complications if the growth plate is involved. ABCs in the temporal bone are a rare occurrence. We report a case of ABC of the right petrous part of the temporal bone in a 38-year-old female patient who presented clinically with headache, facial nerve palsy, and same-sided sensorineural hearing loss. Noncontrast computed tomography (NCCT) scan showed a sharply marginated, smooth hyperdense lytic expansile lesion involving the right petrous bone. Magnetic resonance imaging findings corroborated with the NCCT findings. Surgical resection was performed. External beam radiotherapy was delivered to treat the residual tumor at a dose of 50.4 Gy in 28 fractions by intensity modulated radiation therapy technique over 5 weeks, and the patient was symptom-free on follow-up. This underscores the importance of managing ABCs, particularly those involving craniofacial bones, with surgery followed by radiation therapy for better treatment outcomes and patient survival.
Keywords: aneurysmal bone cyst; temporal bone; case report